THE EFFECT OF EMPLOYEE MORALE AND FACILITIES TOWARD EMPLOYEE EFFICIENCY OF PT ASTRA INTERNATIONAL TBK – DAIHATSU MANADO - Wantania, Yohana I.; Lapian, Stanss L.H.V. Joyce (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Automotive industries in Indonesia are in a fierce competition to win consumers’ choice. It is shown by discount competition which triggered by over production. Thus, the companies always try their best to maximize the performance of its employees in order to achieve their targeted goals to survive and compete in the industry. The objective of this research is to identify the effect of Employee Morale and Facilities toward Employee Efficiency. In this research, the population refers to the employees of Astra International Daihatsu Martadinata Manado which equals to the sample size that are 68 respondents. This research used associative method by using questionnaires and Multiple Regression analysis for data analysis. Result show that Employee Morale and Facilities have significant effect on Employee Efficiency simultaneously and partially. To maximize the efficiency of employees, employees must feel satisfied, happy and accepted with the company supported with high level of work ethic. A company needs to improve the way a company treats their employees, in term of the salary, recognition, rewards, and facilities. Keywords: employee morale, facilities, employee efficiency